2020
DOI: 10.1101/2020.12.23.424111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potentin vitroanti-SARS-CoV-2 activity by gallinamide A and analogues via inhibition of cathepsin L

Abstract: The emergence of SARS-CoV-2 in late 2019, and the subsequent COVID-19 pandemic, has led to substantial mortality, together with mass global disruption. There is an urgent need for novel antiviral drugs for therapeutic or prophylactic application. Cathepsin L is a key host cysteine protease utilized by coronaviruses for cell entry and is recognized as a promising drug target. The marine natural product, gallinamide A and several synthetic analogues, were identified as potent inhibitors of cathepsin L activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…It acts as an irreversible inhibitor of cathepsin L and was highly potent against parasite cathepsin L-like proteases cruzain and falcipain . Cathepsin L inhibition by gallinamide A was causative for a reduced SARS-CoV-2 infection in vitro . Thalassospiramide C, produced by marine bacteria, contains the acrylamide within the 12-membered depsipeptide cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It acts as an irreversible inhibitor of cathepsin L and was highly potent against parasite cathepsin L-like proteases cruzain and falcipain . Cathepsin L inhibition by gallinamide A was causative for a reduced SARS-CoV-2 infection in vitro . Thalassospiramide C, produced by marine bacteria, contains the acrylamide within the 12-membered depsipeptide cycle.…”
Section: Introductionmentioning
confidence: 99%
“…18 Cathepsin L inhibition by gallinamide A was causative for a reduced SARS-CoV-2 infection in vitro. 19 Thalassospiramide C, produced by marine bacteria, contains the acrylamide within the 12-membered depsipeptide cycle. An X-ray crystal structure of its Ndesmethyl derivative (compound 4 in Figure 1; PDB ID: 6HGY) in the active site of cathepsin K corroborated the nucleophilic attack of the active-site cysteine on the β position of the Michael acceptor part.…”
Section: ■ Introductionmentioning
confidence: 99%
“…SARS-CoV-2 has been shown to enter cells through one of two pathways, which require, in addition to its receptor angiotensin-converting enzyme 2 (ACE2), either cathepsins or transmembrane protease serine 2 (TMPRSS2) to efficiently complete its entry step [ 30 , 31 , 32 , 33 ]. Qi and colleagues analyzed expression of ACE2 and TMPRSS2 and found that cell types in the testes that express both proteins include spermatogonia, spermatogonia stem cells, peritubular myoid cells, and testes somatic cells [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several bioactive natural products have been reported that possess a pyrrolinone ring, such as belamide A, caldoramide, and dolastatin 15 . Among them, gallinamide A is one of the best studied and has shown several attractive biological activities, such as to Chagas disease and SARS-CoV-2 infection . The research presented herein provides new insights into this interesting class of natural products.…”
Section: Resultsmentioning
confidence: 99%